2019
DOI: 10.1108/nfs-03-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

Olive cake reduces glycaemia and lipemia and increases antioxidant enzymes in STZ-induced diabetes in rat erythrocytes and tissues

Abstract: Purpose The purpose of this study is to determine the effect of olive cake (CO) on glycaemia and lipemia and lipid peroxidation and antioxidant enzymes activities in erythrocytes and tissues, in streptozotocin (STZ)-induced diabetic rats. Design/methodology/approach Diabetes was induced by a single intraperitoneal injection of STZ (55 mg/kg BW). In total, 12 diabetic D rats, weighing 260 ± 20 g, were divided into two groups fed a casein diet supplemented (D-OC) or not (D) with OC (7.5 per cent), for four wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…In our study, the HFD group showed a decrease in the exogenous and endogenous antioxidant, whereas the treatment of rats with OC increased the GSH level and the SOD, CAT and GPx activities. These results coincide with our previous study (Cherrad et al, 2020) and those of other researchers (Elkotb et al, 2017) where they showed the antioxidant activity of OC in diabetic rats. OC contains a large amount of dietary fiber and phenolic compound like polyphenols, flavonoids, anthocyanins, lignans and phenolic acids (Cea Pavez et al, 2019), which are known for their excellent antioxidant effect.…”
Section: Histological Of Epididymal Fatsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the HFD group showed a decrease in the exogenous and endogenous antioxidant, whereas the treatment of rats with OC increased the GSH level and the SOD, CAT and GPx activities. These results coincide with our previous study (Cherrad et al, 2020) and those of other researchers (Elkotb et al, 2017) where they showed the antioxidant activity of OC in diabetic rats. OC contains a large amount of dietary fiber and phenolic compound like polyphenols, flavonoids, anthocyanins, lignans and phenolic acids (Cea Pavez et al, 2019), which are known for their excellent antioxidant effect.…”
Section: Histological Of Epididymal Fatsupporting
confidence: 93%
“…Our results revealed that OC administration reduced AST, ALT and AKP activities in obese rats, suggesting that this residue attenuated the liver damage caused by HFD. These findings are consistent with the results of Cherrad et al (2020), who reported a decrease in AST and ALT activities in diabetic rats treated with OC. In addition, Liu et al (2011) noted that olive pomace extract inhibited AST, ALT and AKP activities and ameliorated liver injury in hyperlipidemic rats induced by a high cholesterol diet.…”
Section: Histological Of Epididymal Fatsupporting
confidence: 93%
See 1 more Smart Citation
“…This dysregulation in glucose metabolism was ameliorated by supplementation of 1% of Ga in HF-D. Recently, Cherrad et al (2019), revealed that olive cake decreased hyperglycemia in streptozotocin-diabetic rats. But in fact, previous investigations of patients suffering from diabetes, have demonstrated that Ga represented the second highest percentage of medicinal plant consumption (9.9%) after Trigonellafoenum-graecum (13.3%) (Ziyyat et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lins et al (2018) reported that olive leaf extract (an important source of natural antioxidants) was effective in antioxidant activity against different reactive species and protected human erythrocytes against oxidative damage. Furthermore, Cherrad et al (2020) and Zidan et al (2020) stated that olive cake decreased oxidative stress by increasing the antioxidant enzymes activity in erythrocytes, serum, liver, kidney, heart, muscle and brain tissues in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%